TEACHING BANKING AND FINANCE TERMS USING MODERN PEDAGOGICAL TECHNOLOGIES AND IT (Conferencea, 2022)
Active learning shifts the focus of instruction from what the teacher should teach or deliver to students, to what the students should be able to do with the course material. Interactive methods are modern ways of stimulating teaching, representing tools of learning which favor the interchange of ideas, experiences, and knowledge. The purpose of this paper is to present a series of active teaching methods for the accounting data as being an alternative in the process of improving the teaching and learning of the accounting process.